Tinjauan Peran Lembaga Perlindungan Perempuan Indonesia Terhadap Korban Pelecehan Seksual - Gabriella Amanda Tombokan; Hery Firmansyah (LPPM Universitas Ekasakti Padang, 2024)
This research aims to evaluate the effectiveness of women's protection institutions in Indonesia, such as the National Commission on Violence against Women, in providing support and services to victims of sexual harassment. This research also identifies the obstacles and challenges faced by these institutions in carrying out their functions. The research methods used include qualitative analysis of reports, interviews with women's protection agency staff, as well as literature reviews regarding women's protection policies and practices in Indonesia. The research results show that Komnas Perempuan and similar institutions have demonstrated a strong commitment to supporting victims of sexual harassment through various services, including psychological counseling, legal aid, and assistance during the legal process. In addition, education and public awareness campaigns conducted by these institutions have helped change society's views on sexual violence. However, the effectiveness of these services is still limited by obstacles such as limited resources, social stigma, and challenges in law enforcement.